MECHANISMS AND DURATION OF NON-TECTONICALLY ASSISTED MAGMA EMPLACEMENT IN THE UPPER CRUST: THE BLACK MESA PLUTON, HENRY MOUNTAINS, UTAH - de Saint-Blanquat M.; Habert G.; Gleizes G.; Horsman E.; Tikoff B.; Morgan S.S.; Launeau P. (My University, 2006)
A new study of Black Mesa pluton (Henry Mountains, Colorado Plateau, Utah, USA) indicates that it is a classic example of a small upper-crustal pluton assembled over a few years by incremental amalgamation of discrete magma pulses. The results of our petrostructural study of the pluton interior allow us to constrain the geometry, kinematics and timing of the processes. The symmetric internal fabric is interpreted as an evidence for a feeding by below and not laterally. The observed rotation of the lineation, from WNW-ESE on the very top to NNE-SSW below, lead us to propose that the fabric at the base of the pluton is a record of magma infilling process, and the fabric at the very top is a record of the strain due to the relative movement between magma and wallrocks. A consequence is that except at the contact between pluton and wallrocks (top and margins), the stretching direction, recorded by the lineation, is not parallel to the flow direction of the magma i.e. displacement. The Black Mesa pluton is a sheeted laccolith on its western edge and a bysmalith on its eastern edge. This E-W asymmetry in pluton geometry/construction and the symmetrical internal fabric indicates that the apparently different west and east growth histories could have occurred simultaneously. Our field data indicate pluton growth through an asymmetric vertical stacking of sill-like horizontal magma sheets. One-dimensional thermal models of the pluton provide maximum limits on the duration of its growth. We have constrained the number, the thickness, and the frequency of magma pulses with our structural observations, including: (1) the emplacement of the pluton by under-accretion of successive magma pulses, (2) the absence of solid-state deformation textures at internal contacts, and (3) the apparent absence of significant recrystallization in the wallrocks. Our results suggest that the emplacement of the Black Mesa pluton was an extremely rapid event, with a maximum duration on the order of 100 years, which requires a minimum vertical displacement rate of the wallrocks immediately above the pluton greater than 2 m/yr. Finally, our data show that the rates of plutonic and volcanic processes could be similar, a significant result for interpretation of magma transfer in arc systems. © 2006 Elsevier B.V. All rights reserved.
Keywords: BYSMALITH; HENRY MOUNTAINS; LACCOLITH; MAGMA; PLUTON; RATES